Ambient Gases Sensing by Photoluminescence Properties of Porous Silicon - Buakaew, Seangrawee; Ausama, Atthawit; Atiwongsangthong, Narin (My University, 2022)
Ambient gas sensing was responced by photoluminescence intensity properties of porous silicon. Silicon wafer was used as starting material for porous silicon samples, anodization etching process was used to prepare porous silicon layer on p-type silicon substrate. Anodization parameters, the current etchings used between 10 to 40 mA/cm2, with 48% hydrofluoric acid concentration and etching time of 10 minutes. The porous silicon structure were described by using SEM and the porosity of samples by gravimetric technique. The samples were applied as ambient gas sensing were described by photoluminescence intensity at room temperature. The bad of photoluminescence intensity when porous silicon was stored in oxygen ambient gas and the best of photoluminescence intensity was to vacuum.
Keywords: anodization etching; photoluminescence; porous silicon